Effects of Sn on structure and electrical properties of (K0.48Na0.52)0.98Sr0.01NbO3 lead-free piezoceramics - Liu, Yong; Yi, Wentao; Yan, Chunyan; Ma, Jie; Wang, Kunpeng; Fan, Liqun (Ferroelectrics, 2021)
(K0.48Na0.52)0.98Sr0.01NbO3+xmol%SnO2 (KNSN-xSn, x = 0,0.5,1.0,1.5) lead-free piezoceramics were fabricated by the conventional solid state reaction method. The compositional dependence of microstucture, phase structure, defect structure and electrical properties of the ceramics was systemically investigated. XRD patterns revealed that all the ceramic samples possessed pure perovskite structure. At x = 0.5, the ceramic exhibited the optimum electrical properties (d33 = 137 pC/N, kp = 38.5%, tanδ = 0.04, Qm = 114 and Tc = 401 °C), suggesting that this ceramic is a promising lead-free piezoelectric candidate for piezoelectric applications.
Im Titel sind die Zahlen 0.48, 0.52, 0.09, 0.01 und 3 jeweils tiefgestellt